2022
DOI: 10.7717/peerj.14125
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory mechanisms of fatty acids biosynthesis in Armeniaca sibirica seed kernel oil at different developmental stages

Abstract: Background Armeniaca sibirica seed kernel oil is rich in oleic acid and linoleic acid, thus holding potential value as a source of high-quality edible oils. However, some regulatory factors involved in fatty acids accumulation in A. sibirica seed kernels remain largely elusive. Thus, the aim of this study was to elucidate the regulatory mechanisms underlying fatty acids biosynthesis in A. sibirica developing seed kernels. Methods Seed kerne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Tian et al identified 35 lncRNAs regulating castor oil acid biosynthesis through transcriptome analysis [21]. Wu et al identified 13 lncRNAs involved in the regulation of fatty acid biosynthesis through the co-expression network of Armeniaca sibirica kernels at five different developmental stages [22]. The genetic mechanism of fatty acid synthesis in flax has been well reported, with the identification of some key genes in the synthesis pathway [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Tian et al identified 35 lncRNAs regulating castor oil acid biosynthesis through transcriptome analysis [21]. Wu et al identified 13 lncRNAs involved in the regulation of fatty acid biosynthesis through the co-expression network of Armeniaca sibirica kernels at five different developmental stages [22]. The genetic mechanism of fatty acid synthesis in flax has been well reported, with the identification of some key genes in the synthesis pathway [23][24][25].…”
Section: Introductionmentioning
confidence: 99%